Virtual Simulation Experiment Of Potential Energy Of Springs Phet Using Hot-Lab Model: Implications For Education - Muis, Taufik Abdul (PILLAR OF PHYSICS EDUCATION, 2024)
This study explores how effective the Higher Order Thinking Laboratory (HOT-Lab) model is in physics learning, especially on the concept of spring potential energy through virtual PhET simulation. The HOT-Lab model is designed to improve students' critical, creative, and analytical thinking skills and their ability to solve complex problems. This study tries to compare the variation of force and spring constant in a virtual experiment to see its effect on the spring potential energy. The results show that the applied force, spring constant, and potential energy stored in the spring are closely related to each other. Increasing the force or spring constant directly increases the spring potential energy. Virtual PhET simulation has been shown to be a useful tool in visualizing abstract concepts, facilitating variable analysis, and improving students' higher order thinking skills. The results of this study indicate that HOT-Lab has great potential as an innovative method in physics laboratory learning that can develop students' scientific skills in a more in-depth and contextual way.